Substance P–mediated chemokine production promotes monocyte migration. Issue 4 (21st October 2016) - Spitsin, Sergei; Meshki, John; Winters, Angela; Tuluc, Florin; Benton, Tami D; Douglas, Steven D
Abstract : Exposure of human PBMC to substance P results in production of chemokines, including MCP-1, which increases migration of human monocytes. Abstract: The neuropeptide SP has physiologic and pathophysiologic roles in CNS and peripheral tissues and is involved in crosstalk between nervous and immune systems in various conditions, including HIV and SIV infection. Increased SP levels were demonstrated in plasma of HIV + individuals as well as in the CNS of SIV-infected, nonhuman primates. SP increases HIV infection in macrophages through interaction with its receptor, NK1R. The SP effect on immune system is both pro- and anti-inflammatory and includes up-regulation of a number of cytokines and cell receptors. The main goal of this study was to determine whether there is interplay between monocyte exposure to SP and recruitment into sites of inflammation. We now demonstrate that exposure of either human macrophages or PBMCs to SP leads to increased production of chemokines, including MCP-1, for which expression is limited to cells of the myeloid lineage. This effect is inhibited by the NK1R antagonist, aprepitant. Exposure to conditioned medium derived from SP-treated PBMCs resulted in increased monocyte migration through semipermeable membranes and an in vitro human BBB model. Monocyte migration was blocked by anti–MCP-1 antibodies. Our results suggest that increased SP levels associated with HIV and other inflammatory conditions may contribute to increased monocyte migration into the CNS and other tissues through a MCP-1–dependent mechanism.